High bone turnover elevates the risk of denosumab-induced hypocalcemia in women with postmenopausal osteoporosis - Ishikawa K; Nagai T; Sakamoto K; Ohara K; Eguro T; Ito H; Toyoshima Y; Kokaze A; Toyone T; Inagaki K (Therapeutics and Clinical Risk Management, 2016)
Koji Ishikawa,1 Takashi Nagai,1 Keizo Sakamoto,1 Kenji Ohara,2 Takeshi Eguro,1,2 Hiroshi Ito,1 Yoichi Toyoshima,1 Akatsuki Kokaze,3 Tomoaki Toyone,1 Katsunori Inagaki1 1Department of Orthopaedic Surgery, Showa University School of Medicine, Tokyo, 2Department of Orthopaedic Surgery, Yamanashi Red Cross Hospital, Yamanashi, 3Department of Public Health, Showa University School of Medicine, Tokyo, Japan Abstract: Hypocalcemia is the most common major adverse event in patients with osteoporosis receiving the bone resorption inhibitor denosumab; however, limited information is available regarding risk factors of hypocalcemia. Therefore, this study aimed to identify the risk factors of hypocalcemia induced by denosumab treatment for osteoporosis. We retrospectively reviewed the records of patients who had received initial denosumab supplemented with activated vitamin D for osteoporosis. Serum levels of the following bone turnover markers (BTMs) were measured at baseline: bone-specific alkaline phosphatase (BAP), total N-terminal propeptide of type 1 procollagen (P1NP), tartrate-resistant acid phosphatase 5b (TRACP-5b), and urinary cross-linked N-telopeptide of type 1 collagen (NTX). Of the 85 denosumab-treated patients with osteoporosis studied, 22 (25.9%) developed hypocalcemia. Baseline serum total P1NP, TRACP-5b, and urinary NTX were significantly higher in patients with hypocalcemia than in those with normocalcemia following denosumab administration (all P<0.01). Multivariate logistic regression analysis revealed that patients with total P1NP >76.5 µg/L, TRACP-5b >474 mU/dL, or urinary NTX >49.5 nmol bone collagen equivalent/mmol creatinine had a higher risk of hypocalcemia (P<0.01). Our study suggests that denosumab may have a greater impact on serum calcium levels in patients with postmenopausal osteoporosis with higher baseline bone turnover than in patients with postmenopausal osteoporosis with normal baseline bone turnover, because maintenance of normal serum calcium in this subgroup is more dependent on bone resorption. Close monitoring of serum calcium levels is strongly recommended for denosumab-treated patients with high bone turnover, despite supplementation with activated vitamin D and oral calcium. Keywords: denosumab, hypocalcemia, bone turnover, osteoporosis